2010
DOI: 10.3892/ijo_00000702
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer chemopreventive activity of phenethyl isothiocyanate through epigenetic regulation (Review)

Abstract: Abstract. Prostate cancer is one of the most commonly diagnosed cancers in men. The number of affected men is expected to rapidly increase as the population of males over the age of 50 grows worldwide. For patients who are not cured by local treatment and experience metastatic disease, neither androgen ablation nor chemotherapy can abrogate progression and death from androgen-independent/hormonerefractory disease. Therefore, finding strategies for the prevention of prostate cancer initiation and disease progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 53 publications
0
43
0
Order By: Relevance
“…The biological activity of glucosinolates from brassicas in relation to cancer have been extensively reviewed (128,129) , and include induction of drug metabolising enzymes and endogenous anti-oxidants, cell cycle arrest and induction of apoptosis (130,131) . There is also evidence that the isothiocyanate metabolites of glucosinolates can have epigenetic effects through changes in histone acetylation and protection against aberrant CGI methylation in a potentially beneficial manner (132)(133)(134) . Furthermore, it has recently been reported that one glucosinolate derivative, 3,3 0 -diindolylmethane, can modify inflammation in an animal model of colitis (135) .…”
Section: Fruit and Vegetable Consumptionmentioning
confidence: 99%
“…The biological activity of glucosinolates from brassicas in relation to cancer have been extensively reviewed (128,129) , and include induction of drug metabolising enzymes and endogenous anti-oxidants, cell cycle arrest and induction of apoptosis (130,131) . There is also evidence that the isothiocyanate metabolites of glucosinolates can have epigenetic effects through changes in histone acetylation and protection against aberrant CGI methylation in a potentially beneficial manner (132)(133)(134) . Furthermore, it has recently been reported that one glucosinolate derivative, 3,3 0 -diindolylmethane, can modify inflammation in an animal model of colitis (135) .…”
Section: Fruit and Vegetable Consumptionmentioning
confidence: 99%
“…NPC-TW 076 cells at density of 2x10 5 cells/well were placed on 12-well plates and exposed to 10 µM curcumin, or only with vehicle (DMSO, 1% in culture media), and then cells were incubated for 6, 12, 24 and 48 h. After incubation, cells from each treatment were individually harvested by brief trypsinization then washed twice, and then PBS containing 40 µg/ml PI, 0.1 mg/ ml RNase and 0.1% Triton X-100 was added for 30 min at 37˚C and left in the dark. The PI stained cells were analyzed for quantification, cell cycle distribution and sub-G1 phase (apoptosis) by flow cytometry (28,29).…”
Section: Morphological Changes and Percentage Of Viable Cell Examinatmentioning
confidence: 99%
“…NPC-TW 076 cells (2x10 5 ) on 12-well plates were incubated with 10 µM curcumin for 0, 24 and 48 h. Cells from each well were harvested and washed twice with PBS, then substrates were used (PhiPhiLux-G 1 D 2 for caspase-3, OncoImmunin, Inc.) and the activities of caspase-3 was determinated by flow cytometry as described previously (22,27).…”
Section: Determinations Of Viability and Ros In Npc-tw 076 Cells By Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural products have been utilized in cancer prevention because of their ability to induce apoptosis (59,60). The role of dietary products in the prevention of prostate cancer has been confirmed in numerous preclinical and epidemiological studies (57,(61)(62)(63). Dietary agents derived from a natural source are considered pharmacologically safe and have potential use in cancer chemoprevention (3).…”
Section: Discussionmentioning
confidence: 95%